IMPLIKASI CURRENT ACCOUNT SAVINGS ACCOUNT (CASA), BIAYA OPERASIONAL DAN PENDAPATAN OPERASIONAL (BOPO) DAN NON-INTEREST INCOME TERHADAP PROFITABILITAS BANK UMUM - Fajar Andrianto; Wiliam Santoso; Fahrul Riza; Haikal Andrean (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Indonesia's banking sector has grown significantly and is considered one of the largest in Southeast Asia. This is demonstrated by the fact that three Indonesian banks are among the ten largest banks in Southeast Asia by market capitalization. The banking sector is currently facing increasing competition from national banks and foreign bank branches, as well as fintech. In assessing banking performance, profitability is very important. Variables such as Current Account Savings Account (CASA), Operating Expenses to Operating Income (BOPO), and Non-Interest Income affect bank profitability (ROA). This study investigates the effect of CASA, BOPO, and Non-Interest Income (NII) on the profitability of commercial banks in Indonesia. Using the purposive sampling method to select the data sample, this study concentrates on ten banks that belong to Bank Group based on Tier 1 Capital (KBMI) 3 and 4. This study aims to gain a deeper understanding of the variables that affect bank profitability in the context of the Indonesian financial market. This study uses multiple linear regression to analyze the independent variables CASA, BOPO, and non-interest income, and the dependent variable Return on Assets (ROA). The results show that the value of the CASA variable has no direct impact on the value of the ROA variable, the value of the BOPO variable has a negative impact on the value of the ROA variable, and the value of the NII variable has no direct impact on the value of the ROA variable. The results of this study are expected to provide a broader picture for banking management and investors about things that need to be considered related to the variables tested in this study. Keywords: Bank, profitability, CASA, BOPO, ROA